2008
DOI: 10.1111/j.1440-1827.2008.02215.x
|View full text |Cite
|
Sign up to set email alerts
|

RHEB expression in fibroadenomas of the breast

Abstract: Although fibroadenoma is one of the most common types of benign breast tumor, genes specific to the tumor have not been identified. Microarrays were used to identify differentially expressed genes between fibroadenoma and infiltrating ductal carcinoma. The comparative expression of one of the identified genes, RAS homolog enriched in the brain (RHEB), was further explored using reverse transcriptase-polymerase chain reaction (RT-PCR). Microarray analysis was performed on tissue samples from five patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…On a related note, DNA microarray analysis revealed that the Ras homologue enriched in brain (RHEB) protein, also involved in cell growth and differentiation, was expressed at levels more than twofold higher in FAs than in normal tissues. The average RHEB:β-actin ratio of FAs was found to be two times greater than that in infiltrating ductal carcinomas, suggesting RHEB immunohistochemical staining as a possible secondary diagnostic tool to distinguish between the two 66. However, further supporting literature on the role of RHEB in FAs is scant.…”
Section: Tp53 and Ras Mutationsmentioning
confidence: 91%
“…On a related note, DNA microarray analysis revealed that the Ras homologue enriched in brain (RHEB) protein, also involved in cell growth and differentiation, was expressed at levels more than twofold higher in FAs than in normal tissues. The average RHEB:β-actin ratio of FAs was found to be two times greater than that in infiltrating ductal carcinomas, suggesting RHEB immunohistochemical staining as a possible secondary diagnostic tool to distinguish between the two 66. However, further supporting literature on the role of RHEB in FAs is scant.…”
Section: Tp53 and Ras Mutationsmentioning
confidence: 91%
“…Although PT is a type of breast stromal tumor, it is often difficult to distinguish it from FA because these tumors are histologically similar. In previous research, we applied a cDNA microarray method and reported that Ras homolog enriched in brain ( RHEB ), histone deacetylase 1 ( HDAC1 ), and WEE1 homolog ( WEE1 ) are expressed at a two-fold higher level in FA than in normal breast tissues 4. RHEB is associated with tuberous sclerosis, a human genetic disease, and RHEB plays an important role in cell growth and cell-cycle control 5,6.…”
mentioning
confidence: 99%
“…WEE1 functions as a potent tumor suppressor 11. Although numerous genetic studies of breast cancer have been published, few have specifically addressed the genes expressed in these stromal tumors and no studies have reported differences in the expression of these proteins in FA and PT 4,12. Therefore, this study aimed to examine the expression of the RHEB, HDAC1, and WEE1 proteins and to compare the differences in their expression in FA and PT.…”
mentioning
confidence: 99%
“…Two Rheb family members, Rheb1and Rheb2 (also known as RhebL1) have been identified in mammals. Rheb1 was overexpressed in various cancers, such as non-small cell lung cancer, liver cancer, bladder cancer, breast cancer, head and neck cancers, prostate cancer, and acute myeloid leukemia (AML) (46)(47)(48)(49)(50)(51)(52). The human cancer genome data analysis confirmed existence of recurrent Rheb1 mutations (53).…”
Section: Tsc Complex and Rhebmentioning
confidence: 81%